2009
DOI: 10.1016/j.gene.2009.03.014
|View full text |Cite
|
Sign up to set email alerts
|

The homeodomain protein Cux1 interacts with Grg4 to repress p27kip1 expression during kidney development

Abstract: The homeodomain protein Cux1 is highly expressed in the nephrogenic zone of the developing kidney where it functions to regulate cell proliferation. Here we show that Cux1 directly interacts with the co-repressor Grg4 (Groucho 4), a known effector of Notch signaling. Promoter reporter based luciferase assays revealed enhanced repression of p27kip1 promoter activity by Cux1 in the presence of Grg4. Chromatin immunoprecipitation (ChIP) assays demonstrated the direct interaction of Cux1 with p27kip1 in newborn ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 64 publications
(68 reference statements)
2
32
0
Order By: Relevance
“…3, G-I). This expression pattern is consistent with findings reported by Sharma et al (53). Terminal nephron differentiation, marked by expression of AQP2 and Na,K-ATPase, is associated with reduced expression of HDAC1 and HDAC2 FIGURE 2.…”
Section: Spatial Expression Of Hdacs In the Developingsupporting
confidence: 92%
“…3, G-I). This expression pattern is consistent with findings reported by Sharma et al (53). Terminal nephron differentiation, marked by expression of AQP2 and Na,K-ATPase, is associated with reduced expression of HDAC1 and HDAC2 FIGURE 2.…”
Section: Spatial Expression Of Hdacs In the Developingsupporting
confidence: 92%
“…We have recently demonstrated that similar to the Hes, cut homeobox 1 (Cux1) can also associate with TLE protein 4 (TLE4) during kidney development to repress expression of the cyclin kinase inhibitor, p27 [12]. In keeping with the observation that Cux1 is upregulated by Notch intracellular domain, our findings suggested that Cux1 is also an effector of the Notch signaling pathway.…”
Section: Introductionsupporting
confidence: 73%
“…An interaction of CUX1 and HDAC1 has already been postulated in other cell types such as kidney cells and cancer cells, corroborating our findings. 29,42 In line with the concept of CUX1 as a modulator of NF-kB acetylation, Ueda et al 25 described in melanoma cells that CUX1 is able to sequester the acetyltransferase CBP from NFkBp65, leading to reduced acetylation. In our study, we could show that CUX1 decreases induced protein levels of several acetylases, in particular p300, in a TNF-a-dependent manner.…”
Section: Discussionmentioning
confidence: 98%